The 2016 Nobel Memorial Prize in contract theory - Klaus Schmidt (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
Oliver Hart and Bengt Holmström were awarded the 2016 Sveriges Riksbank Prize in Economic Sciences in Memory of Alfred Nobel for their fundamental contributions to contract theory. This article offers a short summary and discussion of their path breaking work.
Keywords: B21; D23; D82; L20; 330; contract theory; nobel prize; optimal incentive schemes; incomplete contracts